ASPECTS REGARDING THE POSSIBILITIES OF PHYSICAL THERAPEUTICAL INTERVENTION IN CEREBRAL MOTOR INFIRMITY - Anca Iacob (Editura Univeristatii "Stefan cel Mare" din Suceava, 2019)
Cerebral motor infirmity or cerebral palsy, as it is called, is a chronic disorder of posture and movement caused by a lesion of the central nervous system. The lesion or dysfunction can occur during pregnancy, during birth or in the first 2-3 years of life. The study was conducted on 3 subjects, selected on the basis of clinical and laboratory manifestations, and was applied in two phases with the same objective, namely the correction of gait and the improvement of limb coordination. At the end of the study there was an increase in the level of neuromotor development in all three subjects which confirms the importance of physical therapy intervention in cerebral motor infirmity.